Vitamins, Minerals and Phytonutrients as Modulators of Canine Immune Function: A Literature Review - Carolina Barroso; António J. M. Fonseca; Ana R. J. Cabrita (Veterinary Sciences)
Trends in the pet food industry are driven by the humanization of pets, favoring the inclusion of functional ingredients or supplements that promote animal health. Several commercial diets claim to include supplements with benefits for dogs’ immune function, but in vivo evidence that supports their efficacy remains limited. This literature review aimed to better understand the current knowledge on the effects of vitamins, minerals and phytonutrients on dogs’ immune function. A total of 27 peer-reviewed articles were identified in PubMed and Web of Science databases. Although vitamin supplementation is often claimed to support immune function, only two studies promoting slight benefits of vitamins C and E were found. The limited research on minerals suggests that organic sources promote a better immune response. Studies evaluating the inclusion of different phytonutrients show that these compounds might exert immunomodulatory and anti-inflammatory effects. Despite the increased popularity of commercial diets claimed to support the immune response of dogs, further research is needed in order to substantiate their effects. This knowledge will contribute to the development of effective diets to enhance immune health in dogs.